2008
DOI: 10.1016/j.visres.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of age-related cuneiform cortical cataracts: The case for mechanical stress

Abstract: We evaluated the gross morphology, location, and fiber cell architecture of equatorial cortical opacities in the aging human lens. Using dark-field stereomicroscopy, we photographed donor lenses in toto and as thick slices. In addition, we investigated the details of the fiber cell architecture using fluorescent staining for membranes and by scanning electron microscopy. We then combined our data with data from recent studies on lens viscoelasticity. We found that small cortical and cuneiform opacities are acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…The extent affected increases with age. In the equatorial plane, they lie consistently at around 500 mm deep to the lens surface and extend centrally to a depth of about 200 mm [64]. The cortex superficial to these opacities is always clear.…”
Section: Age-related Cataract (A) Forms Of Cataractmentioning
confidence: 90%
See 2 more Smart Citations
“…The extent affected increases with age. In the equatorial plane, they lie consistently at around 500 mm deep to the lens surface and extend centrally to a depth of about 200 mm [64]. The cortex superficial to these opacities is always clear.…”
Section: Age-related Cataract (A) Forms Of Cataractmentioning
confidence: 90%
“…They originate in relation to equatorial fractures, perpendicular to the course of large groups of cortical fibres. Fractured ends are slightly swollen and membranes are folded, remotely from the break [74], but the membranes on either side of the fractures are normal, as is the architecture of fibres superficial and deep to the opacities [64]. Their formation involves a repair mechanism that anneals ruptured membranes and seals off the damaged from undamaged parts of the fibres [62].…”
Section: Age-related Cataract (A) Forms Of Cataractmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cortical fiber cells extend from the posterior to the anterior of the lens, this means that opacification begins in the center of a group of fiber cells; the anterior and posterior ends of the same cells remain transparent. Morphological studies found evidence of physical damage early in cortical cataract formation, involving the scission and fragmentation of the cortical fiber cells [8,9] . Cortical cataracts progress in severity by the involvement of increasing numbers of adjacent fiber cells and by the extension of the damage from the center of the cells to their anterior and posterior ends.…”
Section: The 'Natural History' and Etiology Of Age-related Cataractsmentioning
confidence: 99%
“…MRI studies on isolated human lenses [64,65] and preliminary in situ observations in bovine lenses (electronic supplementary material, figure S1) support a restricted entry of water and ions into the deep cortex and nucleus of the lens. Two recent studies [104,105] have shown that early age-related opacities and cortical cataracts have their origin in and stay restricted to the lens cortex, while the lens nucleus remains unaffected, supporting the independence of the lens nucleus behind the barrier compared with the more peripheral regions beyond the barrier. This also suggests that the cortical -nuclear interface forms a barrier preventing or delaying noxious substances from entering the nuclear region and thus postponing occurrence of nuclear lens opacities early in life.…”
Section: Summary and Discussionmentioning
confidence: 92%